Economic analysis of land use changes in forests and rangelands: Developing conservation strategies. (November 2019) - Jahanifar, Komeil; Amirnejad, Hamid; Azadi, Hossein; Adenle, Ademola A.; Scheffran, Jürgen
Highlights: Hyrcanian vegetative area is of national and international importance in terms of economic, environmental and social aspects. This study conducts a cost-benefit analysis of land use change in the forests and rangelands. Results show significant loss of forests and rangelands ecosystem services over a period of 12 years. Results also show that most of land use change scenarios are economically non-viable. The cost-benefit analysis shows changing the forests to agriculture and industrial uses is not feasible. Abstract: Forests and rangelands are economically and environmentally important due to the production of goods and ecosystem services, and any changes in their nature requires a comprehensive evaluation and analysis. The objectives of this study include: a) conducting a cost-benefit analysis of land use change in the forests and rangelands of the Caspian vegetative area with regard to the environmental costs along with other costs and benefits, b) estimating the environmental damage of land use change, and c) developing appropriate strategies for the conservation of the forests and rangelands. The value of costs and benefits of the change was calculated from 2005 to 2016 using the average annual inflation rate up to 2035. The results of the evaluation model show that among the 6 scenarios of land use change, 4 scenarios are completely economically non-viable and two scenarios (forest and rangeland change to residential) are viable with regard to environmental considerations. Moreover, during this period, the change of forest and rangeland for other uses were respectively 43, 732 and 33, 466 ha. Accordingly, considering the average annual value of hectares of forest and rangeland in terms of producing goods and ecological services, the loss incurred was about 334 and 160 million USD.